The effect of the 7DL-7Ae#1L·7Ae#1S translocation on the productivity and quality of spring bread wheat grain - S. N. Sibikeev; E. I. Gultyaeva; A. E. Druzhin; L. V. Andreeva (Вавиловский журнал генетики и селекции)
The 7DL-7Ae#1L·7Ae#1S translocation with the Lr29 gene attracts the attention of bread wheat breeders by its effectiveness against Puccinia triticina. However, its impact on useful agronomic traits has been little studied. In this report, the prebreeding value of 7DL-7Ae#1L·7Ae#1S was studied in analogue lines (ALs) of spring bread wheat cultivars Saratovskaya 68 and Saratovskaya 70 during 2019–2021. The presence of the Lr29 gene was conf irmed by using molecular marker Lr29F24. The ALs with the Lr29 gene were highly resistant to P. triticina against a natural epiphytotics background and in laboratory conditions. 7DL-7Ae#1L·7Ae#1S in Saratovskaya 68 ALs reduced grain productivity in all years of research. On average, the decrease was 35 and 42 %, or in absolute f igures 1163 and 1039 against 1802 kg/ha in the cultivar-recipient. In Saratovskaya 70 ALs, there was a decrease in grain yield in 2019 and 2020, and there were no differences in 2021. On average, the decrease was 18 and 32 %, or in absolute f igures 1101 and 912 against 1342 kg/ha in the cultivar-recipient. The analogues of both cultivars showed a signif icant decrease in the weight of 1000 grains, which ranged from 14 to 20 % for Saratovskaya 68 and 17–18 % for Saratovskaya 70. An increase in the period of germination-earing was noted only in Saratovskaya 68 lines, which averaged 1.3 days. ALs of Saratovskaya 70 had no differences in this trait. 7DL-7Ae#1L·7Ae#1S did not affect plant height and lodging resistance in all ALs. Studies of the bread-making quality in lines with 7DL-7Ae#1L·7Ae#1S revealed a signif icant increase in grain protein and gluten content. As for the effect on the alveograph indicators, there were differences between ALs of both cultivars. While Saratovskaya 68 ALs had a decrease in elasticity and in the ratio of dough tenacity to the extensibility, Saratovskaya 70 lines had an increase in these indicators. All lines increased the f lour strength and the loaves volume, but while Saratovskaya 68 ALs had an increased porosity rating, Saratovskaya 70 ALs had the same rating as the recipient.